Growth and Development of the Uterus and Placenta of Superovulated Gilts - REVOLSON ALEXIUS MEGE; SYAHRUN HAMDANI NASUTION; NASTITI KUSUMORINI; WASMEN MANALU (Bogor Agricultural University, Indonesia, 2007)
Forty eight gilts with average body weight of 107.83 + 5.08 kg were used in experiments to study the use of pregnant mare serum gonadotrophin (PMSG) and human chorionic gonadotrophin (hCG) as superovulation agent in gilts to increase piglet production. Four groups of twelve gilts were injected with PMSG dan hCG dose levels of 0, 600, 1200, and 1800 IU/gilt. Injections were conducted three days before estrus. During gestation, gilts were placed in colony pigpens. On days 15, 35, and 70 of gestation, gilts were slaughtered in order to measure the number of corpus luteum, growth and development of the uterus and placenta. Blood samples were collected to determine progesterone and estradiol concentrations. The resuts showed that superovulation dose levels of 600 to 1200 IU/gilt increased progesterone and estradiol secretions, growth and development of the uterus and placenta in gestation ages of 15, 35, and 70 days. It is concluded that superovulation with dose of 600 to 1200 IU can improve the gilts reproduction. Key words: gilts, superovulation, gestation, progesterone, estradiol, corpus luteum